Marginalization in Globalizing Delhi: Issues of Land, Livelihoods and Health - Acharya, Sanghmitra S.; Sen, Sucharita; Punia, Milap; Reddy, Sunita (Springer India : Imprint: Springer, 2017)
This book analyses how developmental projects in a globalizing Delhi have brought about neglect, exclusion and alienation of certain sections of population, while benefiting others. It discusses the physical, economic and social displacement of people in the city in recent times, which has deprived them of their lands, livelihoods and access to health care. In Delhi and the National Capital Region, beyond the obvious and apparent image of wide roads, flyovers, the metro rail network, high-rises and glittering malls, globalization has brought about skewed and uneven development. A growing middle class and a significant group of an extremely rich section of population steer the ways in which development strategies are planned and implemented. Furthermore, with government control reducing as is inevitable and consistent with a neoliberal policy framework, private players have entered not only the consumer goods sector, but also basic goods and services such as agriculture, health and education. This book explores the effects of such processes, with a specific focus on equity, on the marginalized sections of population in a globalizing megacity. It addresses the themes of land, livelihoods and health as overarching, drawing upon their interlinkages. It traces the changes in the growth of the city in context of these themes and draws inferences from their interconnectedness to examine the current situation of development in Delhi.